National health accounts estimation: lesson from the Nigerian experience (2012)
Objective: This paper seeks to summarize the estimation of two rounds of Nigeria’s National Health Accounts (NHA), 1998-2002 and 2003-2005 and draw some lessons on the NHA methodology and health financing policy challenges towards enhancing government stewardship role in the health sector. Method: The paper uses the results of the two rounds of NHA estimations for Nigeria as basis for analysis. In each round of estimation, three matrices were estimated. Additional three matrices of sub-National Health Accounts were also estimated for 17states in the second round. Results: With Nigeria’s per capital Total Health Expenditure (THE) increasing from US$9.39 in 1998 to US$55,04 in 2005, the THE represent about 5% of GDP. The households accounted for around 68.6% of THE, while government shoulders about 25%. Major lessons learnt relate to skewed spending, challenges of record-keeping and data collection at the federal and state levels, and commitment of government and other stakeholders in ensuring institutionalized procedures for collection, reporting, and retrieval of health financing data. Conclusion: Though NHA results indicate increase in spending on health over time, there is a very high burden on households. Besides, there are institutional challenges inhibiting the estimation process. There is need for government to lessen burden on households to improve its stewardship by increasing its contribution. The institutional capacity need to be strengthen to collect and analyse health expenditure data and interpret results in terms of their policy implication, while government takes ownership of the process to ensure the institutionalization and sustainability of the estimation process.